Penerapan Konseling Individu dengan Teknik Self Management untuk Mengurangi Perilaku Konsumtif pada Santri - Mahesa, Rindes; Suryati, Suryati; Marianti, Lena (Journal of Society Counseling, 2023)
This research is entitled "Application of Individual Counseling with Self Management Techniques to Reduce Consumptive Behavior in Santri Pondok Modern Nurussalam Sidogede Belitang". The aim of this research is to determine the results of implementing self-management counseling in reducing consumptive behavior among students at Pondok Modern Nurussalam Sidogede Belitang. This type of research is field research using a qualitative approach with descriptive methods. Data collection techniques use observation, interviews and documentation methods. The research subjects included 3 students at the Nurussalam Sidogede Belitang Islamic Boarding School who were detected to have consumptive behavior. The research results showed that the clients consisting of 3 Islamic boarding school students at Pondok Modern Nurussalam Sidogede Belitang had consumptive behavior. After carrying out individual counseling in 3 stages, and the middle stage using self-management techniques, there was a change in client behavior in a more positive direction, so it can be concluded that the application of individual counseling with self-management techniques was successful in reducing consumptive behavior in the students of Modern Nurussalam Sidogede Belitang Islamic boarding school.